2006
DOI: 10.3354/meps315113
|View full text |Cite
|
Sign up to set email alerts
|

Microphytobenthos seasonality determines growth and reproduction in intertidal bivalves

Abstract: The annual cycles of phytoplanktonic and microphytobenthic biomasses as food sources for intertidal bivalves were investigated in a temperate estuarine muddy sandflat of Kwangyang Bay (Korea) from January to December 2002. Seasonal patterns in growth and reproductive activity of a suspension-feeder Laternula marilina and a deposit-feeder Moerella rutila were examined in order to assess their relationship with the annual cycles of pelagic and benthic microalgae, and were combined with analyses of δ 13 C and δ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 58 publications
6
48
1
2
Order By: Relevance
“…The pigments were extracted with 5 ml of acetone (90%) for 24 h at -20°C. The subsequent HPLC analysis method is described in Kang et al (2006). MPB cell counts were carried out using an inverted micrcoscope (LEICA); total cell numbers were counted on 150 grids on a grid counting chamber (5250 grids, 500 μl sample).…”
Section: Methodsmentioning
confidence: 99%
“…The pigments were extracted with 5 ml of acetone (90%) for 24 h at -20°C. The subsequent HPLC analysis method is described in Kang et al (2006). MPB cell counts were carried out using an inverted micrcoscope (LEICA); total cell numbers were counted on 150 grids on a grid counting chamber (5250 grids, 500 μl sample).…”
Section: Methodsmentioning
confidence: 99%
“…Tsuchiya & Kurihara 1979, Tenore 1983, see review Lopez & Levinton 1987). However, recent stable isotopic studies have emphasized the trophic importance of locally produced microalgae for benthic detritivores in estuarine and coastal habitats (Sullivan & Moncreiff 1990, Page & Lastra 2003, Yokoyama et al 2005, Kang et al 2006. Only a few studies have shown a significant dietary contribution from terrestrial plant detritus (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…complex (H. atoka, H. diadroma, and H. japonica) and the bivalve Laternula marilina are commonly found in Asian brackish waters , Sato & Nakashima 2003, Kanaya 2005, Kang et al 2006. Hediste spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MPB main ecological functions are carried out when it is organized in the form of biofilms, benthic microalgae can also be resuspended into the water column together with other sedimentary particles throughout the tidal cycle (Koh et al, 2006;Ubertini et al, 2012). This can result in significant enrichment of nearshore waters with a high concentration of chlorophyll a (chl a) that becomes available food for suspension feeders such as the Pacific oyster Crassostrea gigas and other commercially and ecologically important bivalves (Kang et al, 2006;Choy et al, 2009). In coastal zones, despite the high contribution of tidal flats to primary production (Underwood and Kromkamp, 1999), the spatial distribution and temporal dynamic of chl a concentration in intertidal waters has been little studied using ocean color remote sensing so far.…”
Section: Introductionmentioning
confidence: 99%